Th e Accuracy of Delta Neutrophil Index as a Marker of Sepsis Severity Level Compare to Serum Amyloid A - Silvikarina Erfanti Dewi Halim; Rizka Humardewayanti Asdie; Doni Priambodo (Faculty of Medicine Universitas Gadjah Mada, 2019)
Background. Early diagnosis of infection before its progression to become organ dysfunction or circulation failure has an important clinical effect and critical patient outcome. Diagnostic modality used as a gold standard on diagnosing sepsis condition still relies on microbe culture. Microbial culture needed a long duration to grow bacteria in high numbers be identified. The upcoming alternative diagnostic modality used as a marker of sepsis severity level was Delta Neutrophil Index (DNI) and Serum Amyloid A (SAA). There were no references to compare the accuracy of DNI and SAA as a marker of sepsis severity level.Methods. 45 study subjects were patients with sepsis and severe sepsis or septic shock first known when first come to the ER or underwent treatment in the inpatient unit, ICU (Intensive Care Unit) or IMC (Intermediate Care) Sardjito’s Hospital that fulfilled the inclusion and exclusion criteria. The independent variable was DNI and the dependent variable was sepsis severity level. All of blood samples from septic patient undergo DNI and SAA test. Distributed data used the Kolmogorov-Smirnov test. DNI and SAA accuracy used sensitivity, specificity, positive predictive value, negative predictive value, like hood ratio and receiver-operating characteristics (ROC) curve.Results. The study consisted of 45 study subjects. The mean age was 52.98 years. The mean of SAA in this study was 54.39 ± 45.53 mg/L, while the mean of DNI in this study was 12.47 ± 8.79 %. Cut off point DNI 6.85% with value of sensitivity 93%, specificity 70%, positive predictive value (PPV) 79.31%, and negative predictive value (NPV) 87.5%, like hood ratio for a positive test result (LR+) (PLR) 14.28 and like hood ratio for a negative test result (LR-) (NLR) 3.3. Cut off for SAA 54.93 mg/L with value of sensitivity 60%, specificity 56%, positive predictive value (PPV) 52%, negative predictive value (NPV) 64%, like hood ratio for a positive test result (LR+) (PLR) 1.36 and likelihood ratio for a negative test result (LR-) (NLR) 0.71.Conclusions. DNI has better diagnostic accuracy value as a marker of sepsis severity level than SAA.Keywords. Sepsis, sepsis severity level, Delta Neutrophil Index (DNI), Serum Amyloid A (SAA)